Portable lab-on-a-chip platform enabling multiplex recombinant enzyme polymerase amplification detection of H5/H7/H10 avian influenza virus subtypes - Li-guo Liang; Ping Wang; Jiamin Fu; Linwei Zhu; Linfang Cheng; Fumin Liu; Nanping Wu; Lihua Xu; Hangping Yao; Haibo Wu (Poultry Science, 2025)
The zoonotic nature of influenza pathogens creates substantial health security risks, jeopardizing the welfare of interconnected human and animal ecosystems. The H5/H7/H10 avian influenza virus (AIV) variants demonstrate persistent endemicity in poultry reservoirs and recurrent zoonotic jumps precipitating fatal human infections. Therefore, the innovation of multiplex diagnostic platforms integrating expedited processing, enhanced sensitivity, and subtype-specific discrimination has emerged as a pivotal strategy to curb epidemiological escalation. This research introduces a temperature-controlled nucleic acid detection platform utilizing microfluidic technology, enabling concurrent differentiation of H5, H7, and H10 AIV subtypes. Based on the conserved sequences of the hemagglutinin (HA) gene of H5, H7, and H10 AIVs, three sets of primers and probes specific to the subtypes were developed. These were then combined with microfluidic microarray technology and recombinant enzyme polymerase amplification. This combination aimed to create a method for the simultaneous detection of H5, H7, and H10 AIVs for differential diagnostic purposes. The method was distinguished by its specificity, sensitivity, accuracy, and its ability to detect these viruses in clinical samples. The specificity of the method showed that it could detect all strains of H5, H7 and H10 AIVs at the same time, with no cross-reactivity with other subtype influenza viruses or other avian pathogens. The sensitivity results showed that the assay could still detect the three AIV target genes simultaneously at a concentration of 2 copies per reaction. The results of this method for 100 clinical samples were consistent with those produced by quantitative PCR. This integrated detection system for H5/H7/H10 AIV differentiation exhibits exceptional specificity, enhanced sensitivity, rapid turnaround, and streamlined operational procedures, representing a viable solution for prompt pathogen identification during outbreaks.